Financial Literacy: A Study of Rural People in Malwa Region of Punjab - Bansal, Monica (Gyan Management Journal, 2019)
Financial Literacy has been playing a  very important  role in the lives of people,  especially in the  developed nations. A plethora of multifarious and complicated financial services and products at the  disposal compounded by an acute absence of financial knowledge and financial planning among the  masses pose a huge hindrance in the process of smart saving, rational borrowing and wise investment  which might ensure better  retirement benefits and heightened  risk  cover. The development of the  nation does not necessarily guarantee the financial literacy of its people. However, various national  and international agencies are working towards promoting awareness in this matter by conducting  workshops, programmes and seminars etc. on financial education. A lack of financial literacy has huge  adverse effects on the financial decision making of the individual as it leads to a lack of financial  knowledge which  results in  an inability to  plan finances in  an  optimally profitable  and  desirable  manner. On top of it, it impacts the macro-economic concerns adversely as well as it lesser participation  in financial markets, leads to wealth inequality, trenching financial growth and hampering the overall  financial health of a nation. The present research is expected to contribute immensely to the socio economic growth sustenance and overall development of the society.
Keywords: Financial Literacy; Financial Behaviour; Savings; Investment